Algorithm for J-Integral Measurements by Digital Image Correlation; IOP Conference Series: Materials Science and Engineering; Vol. 731 : Advanced Materials for Engineering and Medicine (AMEM-2019) - Titkov V. V.; Eremin A. V. Alexandr Vyacheslavovich; Panin S. V. Sergey Viktorovich; Lyubutin P. S. Pavel Stepanovich; Kozulin A. A. (2020, 2020)
Title screen